2018
DOI: 10.1002/nag.2834
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid ensemble method for improved prediction of slope stability

Abstract: Accurate prediction of slope stability is a significant issue in geomechanics with many artificial intelligence (AI) techniques being utilised. However, the application of AI has not reached its full potential because of the lack of more robust algorithms. In this paper, we proposed a hybrid ensemble method for the improved prediction of slope stability using classifier ensembles and genetic algorithm. Gaussian process classification, quadratic discriminant analysis, support vector machine, artificial neural n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 53 publications
(73 reference statements)
0
18
0
1
Order By: Relevance
“…e search capability of the twosided mapping shrinkage operator is higher than that of the one-sided mapping shrinkage operator. It uses the largest redundant point, the vertex corresponding to the largest pseudogradient, and the largest information entropy to search the solution space, which is better than the basic compound shape method [18]. Although the new optimization algorithm has strong global search ability, its calculation parameters are often difficult to determine, which makes the algorithm easy to fall into local optimal values.…”
Section: Mine Slope Overviewmentioning
confidence: 99%
“…e search capability of the twosided mapping shrinkage operator is higher than that of the one-sided mapping shrinkage operator. It uses the largest redundant point, the vertex corresponding to the largest pseudogradient, and the largest information entropy to search the solution space, which is better than the basic compound shape method [18]. Although the new optimization algorithm has strong global search ability, its calculation parameters are often difficult to determine, which makes the algorithm easy to fall into local optimal values.…”
Section: Mine Slope Overviewmentioning
confidence: 99%
“…A supervised ensemble classifier is a method that combines multiple learning algorithms in machine learning [23, 24]. The classifier ensemble approach aims to form highly accurate ensemble classifiers by combining multiple individual classifiers [25]. Multiple classifier systems, also called ensemble systems, have attracted increasing attention in the computational intelligence and machine learning community.…”
Section: Proposed Thorax Trauma Decision Systemmentioning
confidence: 99%
“…The combination of classifier outputs does not guarantee that a better classification performance will be achieved than the best classifier in the group [26]. However, the accuracy of the ensemble classifier is not less than the average accuracy of all individual classifiers [25].…”
Section: Proposed Thorax Trauma Decision Systemmentioning
confidence: 99%
“…Thus, combining multiple regressors using ensemble learning can enable the final ML model to search in a wide solution space [50]. Previous studies have demonstrated that the ensemble learning can achieve better performance compared with individual ML algorithms [33]- [36], [51].…”
Section: B Regressor Ensemblementioning
confidence: 99%